Selective Recovery and Enrichment of Cobalt from Cobalt-Containing Slag by Carbothermal Reduction - Jiachen Gong; Jian Pan; Jingfu Zhao; Qian Zhang; Guansheng Hao; Yan Liu; Helei Yu (Metals, 2025)
Cobalt ore resources are relatively scarce; thus, the recycling of cobalt-containing slag is highly significant in the economy and society. In this study, the effects of reduction temperature, the reduction agent ratio, reduction time, and particle size on the grade and recovery rate of cobalt in a concentrate were systematically investigated during the carbothermal reduction of cobalt-containing slag. The results revealed that the grades of cobalt, iron, and copper in the concentrate after magnetic separation were 4.02%, 2.48%, and 81.33%, respectively, and the recoveries were 94.17%, 74.80%, and 53.27%, respectively, under the reduction temperature of 1150 °C, the reduction agent ratio of 40%, the reduction time of 2 h, and the particle size of −3.0 mm. Furthermore, through static reduction roasting in a muffle furnace and dynamic reduction roasting in a rotary kiln followed by magnetic separation, a stable cobalt grade, high selective recovery, and effective enrichment were achieved under optimal conditions.